2003
DOI: 10.1002/elps.200390149
|View full text |Cite
|
Sign up to set email alerts
|

High levels of mitochondrial DNA heteroplasmy in single hair roots: Reanalysis and revision

Abstract: The present study demonstrates a reinvestigation of the mitochondrial DNA sequence heteroplasmy, which was previously found by the use of nested polymerase chain reaction (PCR) technique in single hairs of 13 individuals. The direct PCR approach was used for the amplification of mitochondrial DNA and a phylogenetic analysis was applied to both data sets for the verification of the authenticity of sequences. The comparative analysis of the sequencing results obtained from the same hair DNA extracts - but using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 41 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…Various approaches and different primer sets for amplifying and sequencing the coding region and the control region (CR) (or portions thereof) have been reported [21][22][23]. It has been demonstrated that nested PCR analysis can cause an elevated number of phantom mutations [24,25], which in the case of two-stranded sequencing are manifested in pairs of conflicting basecalls at several positions. Such signals could then be misinterpreted as instances of natural heteroplasmy.…”
Section: Introductionmentioning
confidence: 98%
“…Various approaches and different primer sets for amplifying and sequencing the coding region and the control region (CR) (or portions thereof) have been reported [21][22][23]. It has been demonstrated that nested PCR analysis can cause an elevated number of phantom mutations [24,25], which in the case of two-stranded sequencing are manifested in pairs of conflicting basecalls at several positions. Such signals could then be misinterpreted as instances of natural heteroplasmy.…”
Section: Introductionmentioning
confidence: 98%
“…However, it also means that maternally related individuals cannot be distinguished from one another using this technique, reducing its usefulness in criminal investigation when individualisation is required. An additional observation that has received attention in the forensic DNA community is the apparent high level of heteroplasmy that has been observed in mtDNA recovered from hairs [21][22][23][24][25][26][27]. Heteroplasmy in mtDNA sequences derived from hairs is observed as the production of two or more differing DNA sequences arising from a single individual.…”
Section: Dna Analysismentioning
confidence: 95%
“…The properties of mtDNA extracted from hair shafts have been described in depth by several authors [1,5,[7][8][9][10] and a few research articles on the possibility to use STR typing on DNA extracts have also been published in recent last years [11]. Furthermore, McNevin et al [12] recently published an optimized protocol for nuclear DNA extraction from modern hair shafts.…”
Section: Introductionmentioning
confidence: 97%